Biomass-derived nano-laminated Ti3SiC2 MAX phase. Issue 50 (14th November 2022) - Nou, Changwan; Kim, Byeong Geun; Suk, Soo-Young; Choi, Soon-Mok
Abstract : Carbide-based MAX phases, titanium silicon carbide (Ti3 SiC2 ), were synthesized with biomass wastes. Abstract : Carbide-based MAX phases, titanium silicon carbide (Ti3 SiC2 ), were synthesized with Ti, Si, and C elements using a sintering process. Eggshell membranes, which have been generally dumped as domestic wastes, were used as carbon sources in starting materials. After a sintering process at 1500 °C, Ti3 SiC2 phases were mainly formed with a few secondary phases such as TiSi2 and TiC x . The formation and extinction of secondary phases were influenced by the quantities of Si contents in starting materials, which also affected the peak shifts of the Ti3 SiC2 phase in X-ray diffraction spectra. The possible mechanism of this phenomenon was proposed, and the thermoelectric properties of products were also investigated.